Thermo‐mechanical couplings in elastomers – experiments and modelling. Issue 11 (11th August 2014) - Dippel, B.; Johlitz, M.; Lion, A.
Abstract : Elastomers take an important role in many industrial applications. In the automotive industries for example, elastomers are used in various bearings, where they inhibit vibration propagation and thereby significantly enhance driving performance and comfort. Several models have been developed to simulate the material's mechanical response to various stresses and strains a component may undergo during its lifetime. So far, these models are commonly developed under isothermal conditions. Abstract : Elastomers take an important role in many industrial applications. In the automotive industries for example, elastomers are used in various bearings, where they inhibit vibration propagation and thereby significantly enhance driving performance and comfort. Several models have been developed to simulate the material's mechanical response to various stresses and strains a component may undergo during its lifetime. So far, these models are commonly developed under isothermal conditions. In this contribution it is shown that the mechanical properties significantly depend on the temperature and that the material heats up under large dynamic deformations. Therefore, an elastomer's behaviour is not described sufficiently with an isothermal approach, a detailed thermo‐viscoelastic modelling is required. In this contribution, the behaviour of elastomers is experimentally investigated in order to gain informations about the time‐ and temperature‐dependent mechanical properties. We perform different tests on a natural rubber to emphasize the temperature dependence of the equilibrium stress‐strain relation as well as the time‐dependent behaviour in relaxation tests. As it is necessary for parameterising a material model, thermal tests are carried out to determine the specific heat capacity, the thermal expansion coefficient and the thermal conductivity. In a second step, we introduce a material model which is able to represent the temperature‐dependent viscoelastic material behaviour including large deformations, as well as the self‐heating of the material. The model's mechanical parameters are identified on tension tests. In first FE calculations, the applicability of the introduced model is proven by depicting the experimental results of several tension tests at different temperatures. Besides these validations, the self‐heating under dynamic load, depending on the loads amplitude and frequency as well as the surrounding temperature is calculated.